Objective Matrix (OMAX) Analysis to Determine Production Productivity - Indriani, Yulia; Sari, Resy Kumala; Marwa, Safni (Journal of Engineering Science and Technology Management (JES-TM), 2024)
PT. Mitra Bumi is a company operating in the palm oil sector that produces CPO and so far wants to know the level of productivity. OMAX is a partial productivity measurement system developed to monitor productivity in each part of the company with productivity criteria that are appropriate to the existence of that part (objective). Productivity is an important factor to support the survival of a company by analyzing and evaluating the output obtained based on its level of performance during a certain period. To find out the current level of productivity in the production department, it is necessary to measure productivity, because the results of this productivity measurement can be used as a consideration for implementing efforts that can be made to increase the company's productivity. Productivity measurements at PT Mitra Bumi are carried out using the method, objective matrix analysis (OMAX). The criteria used in this research are raw material productivity, effective working hours productivity, machine working hours and production effectiveness. The highest productivity index value was in July with a total value of 112.00%, while the lowest value was in June with a value of -91.33%. The cause and effect diagram is used to determine the causes of the decline in productivity in the CPO production section. As a result, production productivity at PT Mitra Bumi was influenced by factors that caused productivity to decrease, namely damage to the tippler machine, unsuitable raw materials, and less skilled operators